2015
DOI: 10.1371/journal.pone.0118403
|View full text |Cite
|
Sign up to set email alerts
|

Operational Tree Species Mapping in a Diverse Tropical Forest with Airborne Imaging Spectroscopy

Abstract: Remote identification and mapping of canopy tree species can contribute valuable information towards our understanding of ecosystem biodiversity and function over large spatial scales. However, the extreme challenges posed by highly diverse, closed-canopy tropical forests have prevented automated remote species mapping of non-flowering tree crowns in these ecosystems. We set out to identify individuals of three focal canopy tree species amongst a diverse background of tree and liana species on Barro Colorado I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 51 publications
2
133
0
1
Order By: Relevance
“…Higher NDVI threshold has been used in some studies [35], but we selected 0.5 threshold as even the brightest pixels of some of the species in the study area showed lower NDVI values (e.g., Euphorbia kibwezensis).…”
Section: Remote Sensing Data Preprocessingmentioning
confidence: 99%
“…Higher NDVI threshold has been used in some studies [35], but we selected 0.5 threshold as even the brightest pixels of some of the species in the study area showed lower NDVI values (e.g., Euphorbia kibwezensis).…”
Section: Remote Sensing Data Preprocessingmentioning
confidence: 99%
“…The identification of species and successional stage of forests helps to monitor this type of vegetation and Remote Sensing measurements appear as a promising alternative, mainly with imaging spectroscopy using hyperspectral sensors (Féret and Asner, 2013;Baldeck et al, 2015;Näsi et al, 2016;Nevalainen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, partial supervised methods (single-class classification approaches) may provide an effective means to overcome such challenges because they require collection of training data (endmembers) solely from the focal class. These methods are designed to increase detection performance of a single focal class, while reducing the requirement for training data collection, often a necessity in multi-class classification methods [22,23]. For example, Mixture Tuned Matched Filtering (MTMF) focuses on identifying the presence of a single focal class and only requires that training data be collected from the focal class.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Biased Support Vector Machine (BSVM) [30] is another single-class classification approach that has been successfully used to identify focal plant species in the upper canopy, including in tropical forests [23,31]. BSVM has the same general architecture as the binary SVM, but the labeled training data used in BSVM come only from the focal class (detailed description available in [31]).…”
Section: Introductionmentioning
confidence: 99%